ANALISIS DETERMINAN PENGELUARAN KONSUMSI RUMAH TANGGA DI INDONESIA - Najmi Illahi; Melti Roza Adry; Mike Triani (Jurnal Ecogen, 2018)
The study aims to analyze the effect of  disposable income , deposi interes ratet, and education on household expenditure in Indonesia. The analytical method used in this study is to use OLS (Ordinary Least Square) analysis. Tests using statistical tests include t test, F and R squared test and classic assumption test. Where all testing using program tools eviews 8.0. Estimation results show the relationship of independent variables of R2 = 0.9877, meaning that 98.77% of diposible income, deposit rates, and education has impact to household  expenditure in Indonesia. The results of the data analysis show that disposible income  has a positive impact and is significant at α = 5% of household  expenditure in Indonesia. Deposit interest rate variables has negative and significant  impact to household expenditure in Indonesia and education variables has negative and significant, The economic crisis has a positive and significant impact to household consumption expenditure  in IndonesiaKeyword: Disposable Income, Deposit Interes rate,Household Expenditure,Education, Economic crisis